Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1116/1.1667507
|View full text |Cite
|
Sign up to set email alerts
|

Materials growth for InAs high electron mobility transistors and circuits

Abstract: Articles you may be interested inMolecular beam epitaxy growth of high electron mobility InAs/AlSb deep quantum well structure J. Appl. Phys. 114, 013704 (2013); 10.1063/1.4811443 Molecular beam epitaxial growth of metamorphic AlInSb/GaInSb high-electron-mobility-transistor structures on GaAs substrates for low power and high frequency applications J. Appl. Phys. 109, 033706 (2011); 10.1063/1.3544041Suppression of surface segregation of silicon dopants during molecular beam epitaxy of ( 411 ) A In 0.75 Ga 0.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Both the AlGaSb and InAlSb layers provide a large conduction band offset with respect to the InAs, allowing good confinement of electrons. A significant difference between this structure and our earlier HEMTs 18,19 is that the InAlSb upper barrier replaces InAlAs and AlSb. 20 One reason for this change was to avoid the use of pure AlSb, because Miya et al showed that replacing 20-40% of the Al with Ga in AlGaAsSb greatly reduces oxidation.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Both the AlGaSb and InAlSb layers provide a large conduction band offset with respect to the InAs, allowing good confinement of electrons. A significant difference between this structure and our earlier HEMTs 18,19 is that the InAlSb upper barrier replaces InAlAs and AlSb. 20 One reason for this change was to avoid the use of pure AlSb, because Miya et al showed that replacing 20-40% of the Al with Ga in AlGaAsSb greatly reduces oxidation.…”
Section: Resultsmentioning
confidence: 64%
“…The value of x = 0.68 was chosen because it is in reasonable agreement with our nominal value of 0.70 from MBE reflection highenergy electron diffraction (RHEED) oscillation calibrations and because the corresponding relaxation value is close to what we have found in the past for pure AlSb layers of similar thicknesses on GaAs. 18 If R > 0 is assumed for the In y Al 1-y Sb layer, then larger values of y are required and are not consistent with our nominal value. For the InAs layer, the experimental peak position can also be matched for R = 0% if 2% Sb cross-contamination is assumed.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous reports on the growth of InAs layer at higher temperatures 465-510°C close to ͑2 ϫ 4͒ to ͑4 ϫ 2͒ transition is known for its higher mobility and have shown promising device performances. 7,25 However the growths beyond 510°C for particular As-pressure taken up in this study, falls in the bistable region displays pyramid morphology. Meanwhile retaining a smallest interface roughness during the growth of InAs channel at high temperatures, by adjusting the V/III ratio have demonstrated some highest mobility upto 32 000 cm 2 / V s, which is significant for device applications.…”
Section: -23mentioning
confidence: 99%
“…Among the various III-V compound semiconductors, InAs is attracted for long-wavelength, high carrier mobility, 7 high speed, and high frequency applications. 8 Epitaxial thin films for post complementary metal-oxide-semiconductor digital integrated circuits 9 and high performance spin devices [10][11][12] require the surfaces to be atomically smooth with low defect densities in critical conditions.…”
mentioning
confidence: 99%